Muscarinic M1 receptors modulate endotoxemia-induced loss of synaptic plasticity - Živković, Aleksandar; Sedlaczek, Oliver; Haken, Rebecca von; Schmidt, Karsten; Brenner, Thorsten; Weigand, Markus A.; Bading, Hilmar; Bengtson, C. Peter; Hofer, Stefan (Acta Neuropathologica Communications, 2015)
Septic encephalopathy is associated with rapid deterioration of cortical functions. Using magnetic resonance imaging (MRI) we detected functional abnormalities in the hippocampal formation of patients with septic delirium. Hippocampal dysfunction was further investigated in an animal model for sepsis using lipopolysaccharide (LPS) injections to induce endotoxemia in rats, followed by electrophysiological recordings in brain slices. Endotoxemia induced a deficit in long term potentiation which was completely reversed by apamin, a blocker of small conductance calcium-activated potassium (SK) channels, and partly restored by treatment with physostigmine (eserine), an acetylcholinesterase inhibitor, or TBPB, a selective M1 muscarinic acetylcholine receptor agonist. These results suggest a novel role for SK channels in the etiology of endotoxemia and explain why boosting cholinergic function restores deficits in synaptic plasticity. Drugs which enhance cholinergic or M1 activity in the brain may prove beneficial in treatment of septic delirium in the intensive care unit.